Actors' Approach in the Discourse of Rejecting the Threshold for Presidential Candidacy in General Elections in Indonesia - Gani, Mukti Abdul; Fadli, Yusuf; Nurlukman, Adie Dwiyanto; Sarofah, Riska (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
Civil society groups and political parties have disagreed with the presidential threshold article passed by Parliament and the government. The regulation is considered to limit the democratic rights and freedom of the public in choosing, determining, and submitting themselves as presidential candidates. This study aims to explain how actors (agencies) build movements against presidential threshold regulations (structure). The theory used in this study is Anthony Giddens' structuration theory. This research uses qualitative methods by analyzing some content in online media and Constitutional Court rulings related to presidential threshold lawsuits and processing data using the Nvivo 12+ application. The findings of this study indicate that the most crucial aspect of the movement against actors is that it is conducted by challenging the presidential threshold rule before the Constitutional Court, developing public opinion, and holding multiple demonstrations. Second, the size of the presidential threshold rejection vote is based on the future of democracy and freedom, weakening the presidential system and contradicting other regulations. Third, of the many lawsuits filed by the public and political parties, the Constitutional Court has consistently rejected them because the rule is an open legal policy, which means fully being a lawmaker, in this case, in Parliament.